2014
DOI: 10.1017/s0265051714000291
|View full text |Cite
|
Sign up to set email alerts
|

Confidence development in non-music specialist trainee primary teachers after an intensive programme

Abstract: The issue of music teacher training for primary generalist teachers is shared by many\ud countries in the world. We know from a range of studies which factors contribute to\ud teachers’ abilities and confidence, but there are fewer studies that document the possible\ud training approaches and interventions that might improve the outcomes. This article\ud describes an international educational experience addressed to 23 trainee primary teachers\ud coming from Austria, Italy, the Netherlands and Slovenia. The In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 14 publications
0
18
0
2
Order By: Relevance
“…Generalist teachers often lack confidence to teach music in the primary classroom (Biasutti, Hennessy & de Vugt-Jansen, 2015;Joseph, 2014;Baldwin & Beauchamp, 2014;Ballantyne et al 2008;Russell-Bowie, 2009;Holden & Button, 2006). Tertiary music educators are challenged to prepare students for the classroom.…”
Section: Confidencementioning
confidence: 99%
See 1 more Smart Citation
“…Generalist teachers often lack confidence to teach music in the primary classroom (Biasutti, Hennessy & de Vugt-Jansen, 2015;Joseph, 2014;Baldwin & Beauchamp, 2014;Ballantyne et al 2008;Russell-Bowie, 2009;Holden & Button, 2006). Tertiary music educators are challenged to prepare students for the classroom.…”
Section: Confidencementioning
confidence: 99%
“…Therefore, by providing a range of music activities that can be used in the classroom, modeling good practice that empowers students to take risks, and asking questions in a safe and happy environment may be a way for students to build their confidence and competency skills. Creating a learner-centered approach for students that promotes creativity and divergent ways of learning is essential in order for students to be active learners (Biasutti , Hennessy & de Vugt-Jansen, 2015). This environment may foster a sense of wellbeing where students feel happy (Sheldon & Lyubomirksy, 2006).…”
Section: Confidencementioning
confidence: 99%
“…Yet, several research results have revealed serious problems the generalists face when teaching music in basic school (Swanwick, 1992;Hennessy, 2000;Holden & Button, 2006;Wiggins & Wiggins, 2008;Biasutti, 2015;de Vries, 2013;Gravis, 2013;Hallam et al, 2009;Russell-Bowie, 2009;de Vries, 2017).…”
Section: Literature and Theoretical Backgroundmentioning
confidence: 99%
“…It is therefore vital to have a qualified teacher overseeing music lessons. Generalist teachers, or teachers with limited musical experience, have shown a greater capability to deliver a quality music education than, say, music specialists with limited teaching experience (Ofsted, 2012: 18-19), although studies continually address issues about confidence in teaching the subject (Mills, 1989;Hennessy, 2000;Seddon and Biasutti, 2008;Hallam et al, 2009;RussellBowie, 2009;Biasutti, 2010;Garvis, 2013;de Vries, 2013;Biasutti et al, 2015). Furthermore, the teaching of composition is a reported source of uncertainty for specialist as well as generalist teachers (Winters, 2012).…”
Section: Creativity and Curriculummentioning
confidence: 99%